2008
DOI: 10.1080/01411590802092206
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially grown ferroelectric thin films for memory applications (ferroelectric random access memories)

Abstract: Tetragonal Pb(Zr, Ti)O 3 films were epitaxially grown on SrRuO 3 -coated SrTiO 3 substrates by metal organic chemical vapor deposition. Perfect polar-axisoriented 50 nm thick tetragonal films were successfully grown on (100)SrRuO 3 // (100)SrTiO 3 substrates. The single phase of the tetragonal symmetry region was expanded to a Zr/(Zr þ Ti) ratio of around 0.6 for these films but was reduced to around 0.4 when (100)/(001)-mixture oriented 250 nm thick films were obtained. The dependence of spontaneous polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Most research on epitaxial strain control of ferroelectricity in literature has been dominated by ferroelectric thin film heterostructures and devices grown on (00l )-oriented perovskite substrates. Nevertheless, there is increasing interest in the possibility of applying biaxial strain along other crystallographic planes to manipulate the nature of the ferroelectric phase and also engineer complex domain morphologies that are inaccessible in (001)-oriented films [345,346]. In particular, it has been known that complex domain structures with highly-enhanced dielectric and piezoelectric susceptibilities can be engineered by electrically poling bulk single-crystal ferroelectrics along non-polar directions that form equivalent angles with at least two possible directions of spontaneous polarization (sometimes referred to as frustrated poling) [97,[347][348][349][350].…”
Section: Orientation-driven Strain Controlmentioning
confidence: 99%
“…Most research on epitaxial strain control of ferroelectricity in literature has been dominated by ferroelectric thin film heterostructures and devices grown on (00l )-oriented perovskite substrates. Nevertheless, there is increasing interest in the possibility of applying biaxial strain along other crystallographic planes to manipulate the nature of the ferroelectric phase and also engineer complex domain morphologies that are inaccessible in (001)-oriented films [345,346]. In particular, it has been known that complex domain structures with highly-enhanced dielectric and piezoelectric susceptibilities can be engineered by electrically poling bulk single-crystal ferroelectrics along non-polar directions that form equivalent angles with at least two possible directions of spontaneous polarization (sometimes referred to as frustrated poling) [97,[347][348][349][350].…”
Section: Orientation-driven Strain Controlmentioning
confidence: 99%
“…1,2 Recent experimental work has demonstrated that the control of film orientation is one promising and effective approach to manipulate ferroelectric domain structure and properties. 3,4 In studies of thin-film materials, such as the model ferroelectrics PbZr 1−x Ti x O 3 and BiFeO 3 , it has been noted that the variation of film orientation could result in exotic crystal and domain structures and give rise to enhanced ferroelectric susceptibilities. [5][6][7][8] In particular, recent work on (111)-oriented, tetragonal PbZr 0.2 Ti 0.8 O 3 films highlighted how domain-wall contributions to dielectric susceptibilities and ferroelectric switching characteristics can be dramatically tuned with film orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, a significant amount of progress has been achieved in epitaxial growth of thin films and heterostructures of various complex oxides, including ferroelectrics (see e.g. [228][229][230][231][232][233][234][235][236][237]). The literature on strain engineering in ferroelectrics is indeed overwhelming and has led in the recent history, for instance, to the discovery of room-temperature ferroelectricity in strained SrTiO 3 [238].…”
Section: Strain-engineering In Ferroelectric Oxide Thin Filmsmentioning
confidence: 99%